Medieval copto-arabic historiography (13th-14th c.) - Sidarus, Adel Y. (2021)
A good number of studies appears recently dealing with Copto-Arabic Historiography offering new findings or new insights, but also a few text-editions or mere translations. We feel opportune to provide a comprehensive survey of this literature, including a brief outline of the production of the earlier Melkite authors of the 10th-11th centuries, who had a real impact on later Coptic historiography and were together rightly appreciated by Muslim historians. By the way, we will record the Ethiopian translation of a few of those texts between the fourteenth and sixteenth centuries and the impact they exerted over their own historiographic production.